Transformasi Sosial Melalui Edukasi Gizi: Penguatan Peran Komunitas dalam Mengatur Konsumsi Garam dan Kafein pada Ibu Hamil di Posyandu Tenggiri, Kabupaten Batubara - Hadiani Fitri; Athira Demitri; Izmi Arisa Putri Lubis; Winda Sauci Panjaitan (STIKES Columbia Asia Medan, 2025)
Excessive consumption of salt and caffeine during pregnancy can lead to complications such as hypertension, preeclampsia, impaired fetal development, and miscarriage. However, awareness among pregnant women regarding these risks remains low, particularly in regions with limited health literacy such as Batubara Regency. This community service project aimed to enhance pregnant women's understanding of safe salt and caffeine intake through a community-based educational approach at Posyandu Tenggiri. The methods included interactive counseling, group discussions, and pre- and post-test evaluations. The results showed a significant increase in participants’ knowledge, from a pre-test average score of 48.87 to 74.20 in the post-test. Additionally, the activity sparked the emergence of a local change agent and greater family involvement in dietary decisions during pregnancy. This program demonstrated that simple and participatory education can foster social transformation and healthier consumption behavior.